Evaluation of role of biomakers on diabetes mellitus by using human blood samples - G. NAGARAJAPERUMAL; S. MOHAN (International Journal of Pharma and Bio Sciences, 2019)
Diabetes mellitus (DM) is an emergent global metabolic epidemic disease. The diabetic research workers have focused on to find new entity towards treatment of DM associated diseases but only less numbers of active moiety entered the market due not scientifically validated diabetic causative biomarkers. Our aim is to clinically validate biomarkers and to find relationships for improving the therapeutic, diagnostic and management capacity of physician prescribed drugs. Our case-cohort study was conducted in Coimbatore zone included T1 DM, T2 DM associated diseases patients and only DM patients served as a control. 1500 DM patients were collected and observed demographic data, SGOT and SGPT for toxicity monitoring. The survey findings showed that the glucose analysis helped to segregated DM patients (498Numbers & 33.2%), DM associated disease patients (802Numbers & 53.5%) and T2 DM patients (982Numbers & 65.5%). The different levels of SGOT & SGPT results indicates that after the drugs taken, DM + tachyarrthymia patients SGOT levels significantly increased when compared to other associated disease and DM + inflammation patients. SGPT levels were moderately decreased when compared with other diseases. This work will be useful for the researcher’s identification of biomarkers changes on DM and associated diseases, which will be obliging to reduce the DM.